Family across borders social capital and diaspora entrepreneurial preparedness - Karayianni, Eva; Hadjielias, Elias; Glyptis, Loukas (My University, 2021)
Purpose: The purpose of this paper is to study the way in which family ties influence the entrepreneurial preparedness of the diaspora family business owner. Design/methodology/approach: In-depth interviews were carried out with 15 Cypriot family business owners hosted in various countries. The paper draws on social capital theory and uses an abductive analytical approach. Findings: The findings of this paper illustrate that family ties coming from the family across borders play a significant role for diaspora family business owners’ entrepreneurial preparedness. Hidden values deriving from the interpersonal relationships within the family across borders drive the diaspora family business owners to learn upon self-reflection and become entrepreneurially prepared, led by both urgency and esteem. Practical implications: This study provides practical implications for the entrepreneurial preparedness of diaspora family business owners and those who wish to become family business owners in a diaspora context. Originality/value: This study contributes theoretically through the conceptualization of “family across borders social capital” and “diaspora entrepreneurial preparedness”. It also contributes empirically to the fields of diaspora family business, entrepreneurial learning and diaspora entrepreneurship through new knowledge regarding the role of family across borders social capital in the entrepreneurial preparedness of the diaspora family business owner.
Keywords: Family business; Family social capital; Diaspora entrepreneurial learning and preparedness; Diaspora entrepreneurship